Development of a potentially functional chocolate spread containing probiotics and structured triglycerides - de Souza Correia Cozentino, Izabela [UNESP]; Veloso de Paula, Ariela [UNESP]; Augusto Ribeiro, Clovis [UNESP]; Duran Alonso, Jovan [UNESP]; Grimaldi, Renato; Luccas, Valdecir; Taranto, Maria Pia; Cardoso Umbelino Cavallini, Daniela [UNESP] (Elsevier, 2022)
New functional hazelnut and chocolate spreads, containing the probiotic strain Enterococcus faecium CRL 183 and different concentrations of medium-long-medium (MLM)-type structured triacylglycerols (TAGs) were developed. TAGs did not alter the viability of the probiotic strain, during 180 days of storage at 20 °C. The formulations presented similar contents of proteins, lipids, and carbohydrates, water activity below 0.5, thermal stability and were microbiologically stable. The decrease of saturated fat had a negative effect on the rheological properties of the spreads, with reduction on viscosity, Casson yield value and texture parameters. However, only the spread with 75% substitution of vegetable fat by structured TAG showed severe reduction in rheological properties that affected the product spreadability. The use of probiotic strain and replacement of fat (50%) by MLM-type TAG resulted in a new functional chocolate spread with significant increment in medium-chain and unsaturated fatty acids.
Keywords: Chocolate spread; Functional food; Probiotic; Structured triglycerides